The worm has turned. (5th December 2013) - Graham, Bryony J.; Hay, Deborah; Hughes, Jim; Higgs, Doug
<x xml:space="preserve">Abstract</x> Our understanding of biological processes in humans is often based on examination of analogous processes in other organisms. The nematode worm Caenorhabditis elegans has been a particularly valuable model, leading to Nobel prize winning discoveries in development and genetics. Until recently, however, the worm has not been widely used as a model to study transcription due to the lack of a comprehensive catalogue of its RNA transcripts. A recent study by Chen et al. uses next‐generation sequencing to address this issue, mapping the transcription initiation sites in C. elegans and finding many unexpected similarities between the transcription of enhancers and promoters in the worm and mammalian genomes. As well as providing a valuable resource for researchers in the C. elegans community, these findings raise the possibility of using the worm as a model to investigate some key, current questions about transcriptional regulation that remain technically challenging in more complex organisms.